ОРГАНИЗАЦИОННЫЕ МЕРОПРИЯТИЯ ПО ОБЕСПЕЧЕНИЮ БЕЗОПАСНОСТИ ИЗБИРАТЕЛЬНОГО ПРОЦЕССА - Шенцев, Дмитрий Алексеевич (SUPREMANCE OF LAW, 2018)
Based on the analysis of the scientific views of scientists and the norms of the current legislation, the article establishes a range of organizational measures to ensure the safety of the electoral process. It is argued that organizational measures do not provide for the creation, change or abolition of legal norms that are not related to the individual provision of the implementation of the rights or obligations of specific subjects, but their implementation contributes to: directing the activities of the relevant subjects to ensure the safety of the process under study in the right direction; achieving a high level of discipline, expediency and efficiency in the activities of these entities in this area.
Keywords: organization; organizational event; security; electoral process; planning